2022
DOI: 10.1002/slct.202202058
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Involved in Enhancing the Capacitive Energy Storage Characteristics of Poly(vinylidene fluoride) Based Flexible Composites

Abstract: Sasmal acknowledges the Institute Post-Doctoral Fellowship (IPDF) scheme of IIT Madras for providing the financial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 246 publications
(404 reference statements)
0
5
0
Order By: Relevance
“…Capacitive energy storage performance, on the other hand, strongly depends on the electrical breakdown strength (BDS) along with the dielectric permittivity. If k eff is the effective dielectric permittivity, ε 0 is the free space permittivity, and E b is the BDS, then the energy storage density ( U d ) of any linear dielectric capacitor can be expressed by Equation (7) as depicted below [ 42 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Capacitive energy storage performance, on the other hand, strongly depends on the electrical breakdown strength (BDS) along with the dielectric permittivity. If k eff is the effective dielectric permittivity, ε 0 is the free space permittivity, and E b is the BDS, then the energy storage density ( U d ) of any linear dielectric capacitor can be expressed by Equation (7) as depicted below [ 42 ]. …”
Section: Resultsmentioning
confidence: 99%
“…However, in order to show the effect of the materials, the P-E loops of both of the fabricated samples have been compared at a moderate applied electric field of 250 kV/cm. The calculated energy storage density (by calculating areas under desired portion P-E loops) [ 42 ] of NPVDF increased to ~18 mJ/cm 3 with 25% efficiency from a value of ~12 mJ/cm 3 with 25% efficiency. It is true that the obtained values of energy storage parameters are not high enough to be comparable with PVDF-based superior energy storage devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used in a variety of electroactive applications including flexible dielectrics and ferroelectrics, capacitive energy storage, piezoelectric and triboelectric energy harvesting leading to selfpowered mechanosensing, and many others. [1][2][3][4][5] The introduction of various filler materials in the PVDF matrix has been widely reported to enhance its electroactive properties. 6 Along with the improvement of the electro-activity, the included filler material can serve to induce various other properties in the PVDF-based matrix if the filler exhibits specific inherent properties.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, it has been observed that the output performances of PVDF-based flexible devices depend on their different electroactive parameters like the polar phase, dielectric permittivity, ferroelectric polarization, piezoelectric coefficient, electrical breakdown strength, and many others. 3,6 All of these parameters can be tuned by most of the second-phase materials used as fillers in its matrix. There have been wideranging attempts to correlate different physiochemical properties of fillers with the output performances of their PVDFbased composites.…”
Section: Introductionmentioning
confidence: 99%